(untitled) (Eurasian Journal of Ecology, 2016)
The article presents data on the analysis of samples of water and soil on the content of the nine heavy metals from the territory of the newly opened National Park Zhongar Alatau. Samples were taken from the parking lot of tourists, as well as from nearby rivers to it and their shores. Analyses were performed using standard techniques. Identified soil contamination parking Cu, Zn, Ni, Fe, Co, and water streams contain Pb and Fe concentrations significantly above the MCL for drinking water. Reducing pollution of this is possiblethrough the development of an environmental culture.